2008
DOI: 10.1186/1742-4690-5-20
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel resistance (E40F) and compensatory (K43E) substitution in HIV-1 reverse transcriptase

Abstract: In conclusion, we have identified a novel resistance (E40F) and compensatory (K43E) change in HIV-1 RT. Further research is indicated to analyse the clinical importance of these changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 46 publications
(37 reference statements)
2
6
0
Order By: Relevance
“…This increase is probably only transient and is expected to be reversed at reinitiation of therapy. Our findings of stable RC values over the 12-week course of salvage therapy in no-ARDFP patients confirm previous observations that accumulation of resistance-associated mutations during partially suppressive HAART (as in many patients in that group) is not likely to induce further RC decline, probably because secondary 'compensatory' mutations appear [28,29]. Among patients not undergoing a treatment interruption, PSS was correlated with baseline RC and was highly predictive of virologic response to salvage ARV regimen up to week 48, after controlling for other baseline variables: RC, CD4 cell count and viral load.…”
Section: Discussionsupporting
confidence: 79%
“…This increase is probably only transient and is expected to be reversed at reinitiation of therapy. Our findings of stable RC values over the 12-week course of salvage therapy in no-ARDFP patients confirm previous observations that accumulation of resistance-associated mutations during partially suppressive HAART (as in many patients in that group) is not likely to induce further RC decline, probably because secondary 'compensatory' mutations appear [28,29]. Among patients not undergoing a treatment interruption, PSS was correlated with baseline RC and was highly predictive of virologic response to salvage ARV regimen up to week 48, after controlling for other baseline variables: RC, CD4 cell count and viral load.…”
Section: Discussionsupporting
confidence: 79%
“…For example, Huigen et al found that the K43E mutation alone did not increase the levels of resistance, but showed a compensatory role when combined with E40F. 18 A study by Cane et al showed that K43E was detected in only 1% of HIV-1 patients with no TAMs but in 24% of samples with four or more TAMs, 16 whereas in the present study the mutation was seen in 83.3% of newly diagnosed, therapynaive HIV-1 patients who were infected with CRF01_AE, and in none of the CRF07_BC patients. It is possible that the K43E change was a subtype-specific polymorphic mutation that was found more frequently in CRF01_AE than CRF07_BC.…”
Section: Discussionmentioning
confidence: 99%
“…Several of these mutations occur at known NRTI resistance positions: K65N, D67G/E/S/T, K70Q/N/G/S/T, L74I, V75M/A/S, and K219N/R/W/ D/H (2,4,11,25,30,37). Others are at novel positions in the 5= polymerase coding domain: E40F, K43E/Q/N, E44D/A, V118I, E203K, H208Y, D218E, K223Q/E, and L228H/R (9, 12, 33) (13,30). Finally, several mutations 3= to the polymerase coding domain facilitate nucleotide excision, presumably by slowing enzymatic translocation, allowing more time for nucleoside reverse transcriptase inhibitor (NRTI) excision (19).…”
Section: Discussionmentioning
confidence: 99%